The Hokkaido Birth Cohort Study on Environment and Children's Health: cohort profile-updated 2017 - Reiko Kishi; Atsuko Araki; Machiko Minatoya; Tomoyuki Hanaoka; Chihiro Miyashita; Sachiko Itoh; Sumitaka Kobayashi; Yu Ait Bamai; Keiko Yamazaki; Ryu Miura; Naomi Tamura; Kumiko Ito; et al. (Komiyama Printing Co. Ltd, 2017)
Abstract The Hokkaido Study on Environment and Children's Health is an ongoing study consisting of two birth cohorts of different population sizes: the Sapporo cohort and the Hokkaido cohort. Our primary study goals are (1) to examine the effects of low-level environmental chemical exposures on birth outcomes, including birth defects and growth retardation; (2) to follow the development of allergies, infectious diseases, and neurobehavioral developmental disorders and perform a longitudinal observation of child development; (3) to identify high-risk groups based on genetic susceptibility to environmental chemicals; and (4) to identify the additive effects of various chemicals, including tobacco smoking. The purpose of this report is to update the progress of the Hokkaido Study, to summarize the recent results, and to suggest future directions. In particular, this report provides the basic characteristics of the cohort populations, discusses the population remaining in the cohorts and those who were lost to follow-up at birth, and introduces the newly added follow-up studies and case-cohort study design. In the Sapporo cohort of 514 enrolled pregnant women, various specimens, including maternal and cord blood, maternal hair, and breast milk, were collected for the assessment of exposures to dioxins, polychlorinated biphenyls, organochlorine pesticides, perfluoroalkyl substances, phthalates, bisphenol A, and methylmercury. As follow-ups, face-to-face neurobehavioral developmental tests were conducted at several different ages. In the Hokkaido cohort of 20,926 enrolled pregnant women, the prevalence of complicated pregnancies and birth outcomes, such as miscarriage, stillbirth, low birth weight, preterm birth, and small for gestational age were examined. The levels of exposure to environmental chemicals were relatively low in these study populations compared to those reported previously. We also studied environmental chemical exposure in association with health outcomes, including birth size, neonatal hormone levels, neurobehavioral development, asthma, allergies, and infectious diseases. In addition, genetic and epigenetic analyses were conducted. The results of this study demonstrate the effects of environmental chemical exposures on genetically susceptible populations and on DNA methylation. Further study and continuous follow-up are necessary to elucidate the combined effects of chemical exposure on health outcomes.